Rabies: Knowledge and Practices Regarding Rabies in Rural Communities of the Brazilian Amazon Basin - da Costa, Lanna Jamile Corrêa (PLoS Negl Trop Dis, 2016)
BACKGROUND: The occurrence of outbreaks of human rabies transmitted by Desmodus rotundus in Brazil in 2004 and 2005 reinforced the need for further research into this zoonosis. Studies of knowledge and practices related to the disease will help to define strategies for the avoidance of new cases, through the identification of gaps that may affect the preventive practices. METHODOLOGY/PRINCIPAL FINDINGS: A semi-structured questionnaire was applied to 681 residents of twelve communities of northeastern Pará state involved in the 2004 and 2005 outbreaks mentioned above. The objective was to evaluate the local knowledge and practices related to the disease. We found a highly significant difference (p<0.0001) in the knowledge of rabies among education levels, indicating that education is a primary determinant of knowledge on this disease. More than half of the respondents (63%) recognized the seriousness of the zoonosis, and 50% were aware of the importance of bats for its transmission, although few individuals (11%) were familiar with the symptoms, and only 40% knew methods of prevention. Even so, 70% of pet owners maintained their animals vaccinated, and 52% of the respondents bitten by bats had received post-exposure vaccination. Most of the respondents (57%) reported being familiarized with rabies through informal discussions, and only a few (23%) mentioned public health agents as the source of their information. CONCLUSION/SIGNIFICANCE: We identified many gaps in the knowledge and practices of the respondents regarding rabies. This may be the result of the reduced participation of public health agents in the transfer of details about the disease. The lack of knowledge may be a direct determinant in the occurrence of new outbreaks. Given these findings, there is a clear need for specific educational initiatives involving the local population and the public health entities, with the primary aim of contributing to the prevention of rabies.